Respostas
respondido por:
2
a5=100
a4=90
a3=80
a2=70
a1=60
a4=90
a3=80
a2=70
a1=60
respondido por:
4
an = a1 + ( n-1)r
onde r = 10 é a razão da Progressão aritmética e a1 é o primeiro termo
então temos:
a5 = a1 + ( 5-1)r , a5 = 100 , r=10
100 = a1 + 4(10)
portanto a1 = 100 - 40
a1 = 60.
onde r = 10 é a razão da Progressão aritmética e a1 é o primeiro termo
então temos:
a5 = a1 + ( 5-1)r , a5 = 100 , r=10
100 = a1 + 4(10)
portanto a1 = 100 - 40
a1 = 60.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás